Relations of trauma exposure with current religiousness and spirituality - Lee, Sharon Y. (Mental health, religion & culture, 2016)
Many theorists posit that religiousness/spirituality (RS) may change after trauma. However, empirical findings regarding RS following trauma are inconclusive. The present study examined the relationship between potentially traumatic events (PTEs) and current RS by considering the cumulative effect of PTEs and multiple dimensions of RS. In our sample of 245 undergraduates (60% female, 79% White), there were no differences in RS between participants who did and did not have PTEs. When analysed as a continuous variable, the number of PTEs was positively correlated with many RS dimensions (i.e., daily spiritual experiences, religious strain, religious comfort, provident and challenging God images, belief in God) but not all (i.e., organised religious involvement, belief in afterlife, benevolent God image). These results suggest that PTEs relate distinctly to different aspects of RS and that examining multiple dimensions of RS may be a more informative way of studying this association.